PREGNANT WOMEN EMPOWERMENT IN MONITORING FETAL WELLBEING THROUGH FETAL MOVEMENT COUNT MOBILE APPLICATION - Ika Yudianti; Dessy Amelia; Nur Eva Aristina; Nina Primasari (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2022)
Fetal movement is one of the main indicators of fetal well-being in the womb. For this reason, every pregnant woman should be able to calculate and interpret the results of fetal movement calculations every day, so that early detection of fetal pathology can be identified by the family. Most pregnant women are not used to it and have not received information about how to calculate fetal movement. Another obstacle in calculating fetal movements is the forgetting factor. For this reason, a tool is needed to familiarize mothers with counting fetal movements every day. Existing tools still have some drawbacks. This study aims to develop an android-based application called